Baicalein induces functional hypoxia-inducible factor-1 alpha and angiogenesis - Cho, Hyunju; Lee, Ho-Youl; Ahn, Dae-Ro; Kim, Sang Yoon; Kim, Sunyun; Lee, Keun Byeol; Lee, You Mie; Park, Hyunsung; Yang, Eun Gyeong (AMER SOC PHARMACOLOGY EXPERIMENTAL THERAPEUTICS, 2008)
Targeting the oxygen-sensing mechanisms of the hypoxia-inducible factor (HIF) pathway provides pharmacological ways of manipulating the HIF response. Because HIF-1 alpha-specific prolyl-4 hydroxylases (PHDs) prime degradation of HIF-1 alpha, we have made an effort to find a small molecule capable of up-regulating the HIF pathway by inhibiting prolyl hydroxylation. Through an in vitro high-throughput screen, we have discovered a PHD2 inhibitor baicalein, which is also found to abrogate asparaginyl hydroxylation of HIF-1 alpha. Such inhibitory effects are reversed by the addition of excess 2-oxoglutarate and iron(II), suggesting the involvement of baicalein's binding at the enzyme active sites, which has also been corroborated by spectroscopic binding assays between baicalein and enzyme. In addition, baicalein suppresses ubiquitination of HIF-1 alpha, which works in concert with the inhibition of the HIF-specific hydroxylases to increase the HIF-1 alpha content, leading to induction of HIF-1-mediated reporter gene activity and target gene transcription in tissue culture cells, whereas it induces HIF-independent activation of other genes. Furthermore, in vivo organ models based on the chick chorioallantoic membrane assay demonstrate that baicalein promotes new blood vessel formation. Together, our results indicate that baicalein possesses a proangiogenic potential and thus might have the therapeutic utility in the treatment of ischemic diseases.
Keywords: HYPOXIA-INDUCIBLE FACTOR; ENDOTHELIAL GROWTH-FACTOR; PROLYL HYDROXYLASE; SCUTELLARIA-BAICALENSIS; CELL PROLIFERATION; RESPONSE PATHWAY; CANCER CELLS; HIF; INHIBITION; HIF-1-ALPHA